A Personality Study of The Main Character In Luca Movie - Dian Ayu Lestari, Ni Putu; Nova Winarta, Ida Bagus Gde (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 23 No 2 (2023)DO - 10.24843/PJIIB.2023.v23.i02.p01, 2023)
Nowadays we can meet people with various types of personality that are diverse and sometimes unique. Therefore, this research entitled "A Personality Study of the Main Character in Luca Movie" has the main objective to analyze the personality of the main character in a movie entitled ‘Luca’. The method used is the documentation method to capture every scene and dialogue, which will be used as data in this study, and after that it will be continued by describing each data obtained in order to get a clearer understanding. This research uses the personality type theory proposed by Jason Gale in his book entitled ‘How to Analyze People Ultimate Guide; Learn Psychology, Body Language, Perception, Types of Personalities, and Universal Rules’. This movie has three characters as the main characters; Luca Paguro, Alberto Scorfano, and Giulia Marcovando. The results of this study indicate that Luca Paguro is the protagonist of this story and he also has introverted and feeler nature. While his friend, Alberto Scorfano is an adventurer, he is an extrovert who is also a censor. And lastly, Giulia Marcovando is an extroverted censorship type girl and a defender as seen from how she tries to protect Luca and Alberto.